(3cJGH aj GdcjejGAs
(3ChdgG (B:s
(3HYO GdHSedI fHJOF HYhf Gdgd HUaI GdMceI GdeHGQcI GdJj CdaR ajgG GdMceGA hSehgG HCSeGA cKjQI eNJdaI hZjQ eNJdaI s
(3BNQgG (B:s
(3BNQ GdehLhO UaI Yed GdGSQH jDNP ef GdGSQH YTQ OQGge hef GdQGSNJ SJjf OQgekG s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
Keywords: (3eJaQbGJs